2018
DOI: 10.1038/s41598-018-25557-8
|View full text |Cite|
|
Sign up to set email alerts
|

Classical and alternative complement activation on photoreceptor outer segments drives monocyte-dependent retinal atrophy

Abstract: Geographic atrophy (GA), the advanced form of dry age-related macular degeneration (AMD), is characterized by progressive loss of retinal pigment epithelium cells and photoreceptors in the setting of characteristic extracellular deposits and remains a serious unmet medical need. While genetic predisposition to AMD is dominated by polymorphisms in complement genes, it remains unclear how complement activation contributes to retinal atrophy. Here we demonstrate that complement is activated on photoreceptor outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 68 publications
2
57
0
Order By: Relevance
“… 15 Recent data from tissue from donors with AMD and animal models suggested that complement activation on photoreceptors contributed to the loss of photoreceptor function in C5a-dependent recruitment of peripheral blood monocytes independent of resident microglia. 68 A previous report failed to detect a significant number of inflammatory cells in the early stages of AMD. 69 However, the density of Iba1+ cells was significantly increased in the retina and choroid of sections from three AMD donor 70 and in tissue from a donor with advanced-stage AMD.…”
Section: Discussionmentioning
confidence: 94%
“… 15 Recent data from tissue from donors with AMD and animal models suggested that complement activation on photoreceptors contributed to the loss of photoreceptor function in C5a-dependent recruitment of peripheral blood monocytes independent of resident microglia. 68 A previous report failed to detect a significant number of inflammatory cells in the early stages of AMD. 69 However, the density of Iba1+ cells was significantly increased in the retina and choroid of sections from three AMD donor 70 and in tissue from a donor with advanced-stage AMD.…”
Section: Discussionmentioning
confidence: 94%
“…However, corresponding to the diversity of complement-related effector functions, the net impact of complement activation on neural outcomes has been quite varied, with complement inhibition by genetic or pharmacological means producing both positive and negative outcomes depending on the context. In the majority of studies, genetic and/or pharmacological inhibition of complement components, such as C1q ( Silverman et al, 2016 ; Jiao et al, 2018 ), C3 ( Jha et al, 2011 ; Natoli et al, 2017 ; Bosco et al, 2018 ; Katschke et al, 2018 ), CFB, and complement factor d (CFD; Sweigard et al, 2015 ), have decreased retinal neurodegeneration, and genetic ablation of complement components in models of Alzheimer’s disease ( Hong et al, 2016 ; Shi et al, 2017 ) and frontotemporal dementia ( Lui et al, 2016 ) has decreased neural loss in the brain. These findings indicate that complement-mediated responses triggered in these injury contexts are likely excessive and/or inappropriately regulated and culminate in worsened overall synaptic degeneration and neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…However, corresponding to the diversity of complement-related effector functions, the net impact of complement activation on neural outcomes has been quite varied, with complement inhibition by genetic or pharmacological means producing both positive and negative outcomes depending on the context. In the majority of studies, complement activation has been associated with exacerbated neurodegeneration; genetic and/or pharmacological inhibition of complement components, such as C1q (37, 38), C3 (22,(39)(40)(41), CFB and CFD (42), have decreased retinal neurodegeneration, while genetic ablation complement components in models of Alzheimer's disease (AD) (29,43) and frontotemporal dementia (44), have decreased neural loss in the brain.…”
Section: Discussionmentioning
confidence: 99%